2015
DOI: 10.1128/aac.00763-15
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Combined Antibiotic-Antibody Treatment Eliminates Toxicity from Shiga Toxin-Producing Escherichia coli

Abstract: bTreating Shiga toxin-producing Escherichia coli (STEC) gastrointestinal infections is difficult. The utility of antibiotics for STEC treatment is controversial, since antibiotic resistance among STEC isolates is widespread and certain antibiotics dramatically increase the expression of Shiga toxins (Stxs), which are some of the most important virulence factors in STEC. Stxs contribute to life-threatening hemolytic uremic syndrome (HUS), which develops in considerable proportions of patients with STEC infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…β-lactam antimicrobials, especially at sub-inhibitory concentrations, can increase Shiga toxin production and release by O157 bacteria in vitro [ 6 , 7 , 9 , 20 ]. The specific mechanism(s) for these effects have not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…β-lactam antimicrobials, especially at sub-inhibitory concentrations, can increase Shiga toxin production and release by O157 bacteria in vitro [ 6 , 7 , 9 , 20 ]. The specific mechanism(s) for these effects have not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Stx receptor analogs ( Nishikawa et al, 2002 , 2005 ) and antibodies specific to the toxins has also been reported. A strategy that combined antibiotics and antibody specific for the Stx appeared effective in in vitro experiments ( Skinner et al, 2015 ). The small molecule Retro-2 cycl that functions by inhibiting host retrograde trafficking is effective against infections caused by the EHEC strain O104:H4 in a mouse disease model ( Secher et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were then washed with TBST three times at room temperature for 3 min with gentle agitation. Primary antibody solution containing antibody to Stx1-1 or Stx2-5 (Skinner et al, 2014, 2015; Wang et al, 2016) at dilutions 1:1000 in TBST with 5% NFDM was added to blots and allowed to incubate overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%